Genetic variants of α-synuclein are not associated with essential tremor - Ross, Owen A. (2011)
BACKGROUND: Given the overlap between Parkinson disease and essential tremor, we examined genetic variants in α-synuclein (SNCA) as risk determinants for essential tremor. METHODS: Samples from 661 essential tremor subjects and 1,316 control subjects from four participating North American sites were included in this study. Parkinson disease samples (n=427) were compared against controls for two cohorts. Twenty variants were selected for association analysis within the SNCA locus. Individual logistic regression analyses against essential tremor diagnosis and then combined using meta-analysis was run for each variant. RESULTS: Our results do not show a significant association between variants in the SNCA locus and risk of essential tremor, while the established association of SNCA variants with Parkinson disease risk was observed. CONCLUSIONS: While genetic factors are likely to play a large role in essential tremor pathogenesis our results do not support a role for common SNCA genetic variants in risk for essential tremor.